Global Crises: Gendered Vulnerabilities of Structural Inequality, Environmental Performance, and Modern Slavery - Cameron, Erinn C. (Hu Arenas, 2021)
Climate change and modern slavery are two of the most significant human rights crises of our time. Women and children are disproportionately vulnerable to such crises, which are intensified under inequitable social conditions and driven by structural barriers to female equality. No research has yet looked at the complex relationship between climate crisis, structural gender inequality, human insecurity, and vulnerability to modern slavery. Our research examined the relationship between environmental stressors associated with climate change, selected structural inequalities, and the estimated prevalence of modern slavery cases across 180 countries. Regression analysis revealed significant results. These findings suggest that indicators of poor environmental health may exacerbate structural social inequalities and increase women’s risk of falling victim to modern slavery. Results showed that women’s share of seats in parliament, education for women, tree cover loss, agricultural management, and air quality assumed more substantial roles in this prediction. Awareness of the unique relationship between environmental indicators of climate change, gender inequality, and modern slavery provides a meaningful contribution to our understanding of factors driving human exploitation. Additionally, we propose a gender analysis of environmental stressors to address both the climate crisis and structural inequalities that increases female vulnerability to insecurity.